2021
DOI: 10.1111/mms.12841
|View full text |Cite
|
Sign up to set email alerts
|

Translocations maintain genetic diversity and increase connectivity in sea otters, Enhydra lutris

Abstract: Sea otters, Enhydra lutris, were once abundant along the nearshore areas of the North Pacific. The international maritime fur trade that ended in 1911 left 13 small remnant populations with low genetic diversity. Subsequent translocations into previously occupied habitat resulted in several reintroduced populations along the coast of North America. We sampled sea otters between 2008 and 2011 throughout much of their current range and used 19 nuclear microsatellite markers to evaluate genetic diversity, populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 81 publications
2
6
0
Order By: Relevance
“…Individuals from each sampling location clustered by genotypes in both PCA (Figure 1b) and faststructure (Figure 1c) analyses, and values of F ST increased with distance between populations (Figure D; Table ), agreeing with previous studies (Larson et al, 2012, 2021; Larson, Jameson, Bodkin, et al, 2002). Sea otters in California are the most divergent population and represent the only surviving remnant of the southern sea otter subspecies ( Enhydra lutris nereis ) (Figure 1b,d).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Individuals from each sampling location clustered by genotypes in both PCA (Figure 1b) and faststructure (Figure 1c) analyses, and values of F ST increased with distance between populations (Figure D; Table ), agreeing with previous studies (Larson et al, 2012, 2021; Larson, Jameson, Bodkin, et al, 2002). Sea otters in California are the most divergent population and represent the only surviving remnant of the southern sea otter subspecies ( Enhydra lutris nereis ) (Figure 1b,d).…”
Section: Resultssupporting
confidence: 90%
“…We found that the geographically driven population structure of sea otter populations remained after the fur trade bottlenecks, leading to five broad geographical groupings in our sample: the Kuril Islands, Commander Islands, western Aleutian Islands, south central Alaska, and California. This shows that a key element of the successful restoration of sea otters was their survival and numerical increase from small remnant populations distributed throughout their geographical range rather than long‐distance dispersal (Larson, Jameson, Bodkin, et al, 2002; Larson et al, 2012, 2021). This fortuitous survival allowed both rapid range‐wide restoration of former abundance and preserved historical genetic structure and perhaps even local specializations that enhanced survival (Fujii et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from sea otter morphological and genetic studies 17 has shown population structuring across their range and led to the recognition of different subspecies for the Commander Islands and the Aleutian islands 18 lending support to the idea of ecological barriers at this geographic location. Although we acknowledge considerable differences in life history traits between these species, sea otters are the only other marine mammal restricted to nearshore coastal waters of the North Pacific, sharing a remarkably overlapping distribution with sea cows 19 .…”
mentioning
confidence: 94%
“…To evaluate the ecological influence the Steller's sea cow may have exerted over kelp forests around the North Pacific Rim 11 we have been preparing updated range maps considering the species glacial and interglacial ranges. These nearshore habitat maps are grounded in the fossil record and guided by bioindicators of kelp habitat, oceanographic data, and various lines of ecological evidence [9][10][11][12][13][14][15][16][17][18][19][20] (Fig. 1).…”
mentioning
confidence: 99%